Justice in Jeopardy? The Relationship Between Sentencing and Confiscation Orders under the Proceeds of Crime Act 1991 - Moreland, Louise (Victoria University of Wellington Law Review, 2000)
The Proceeds of Crime Act 1991 was enacted in response to concern about increasing serious and organised crime. The Act aims to reduce such crime by providing an additional deterrent to traditional punishments by confiscating the profits of and property used to commit serious offences. This article considers the relationship between confiscation under the Act and sentencing. It is argued that the courts’ approach to the application of the Act has not always been consistent, and that it is essential that the courts take forfeiture of property used to commit offences into account when sentencing in order to avoid potentially oppressive and arbitrary results.